Pesticide Safety Miniposter: Apply the Correct Amount - Rebecca W. Baldwin; Stephanie K. Larrick Hill; Philip Koehler; W. Walker; J. C. Medley (EDIS)
Pest managers must know the proper amount of pesticide product to apply. This poster acquaints new pest control technicians with the basic process of following label instructions to properly dilute pesticides, and it walks technicians through two types of basic equipment calibration. The poster has quick response (QR) codes that link smartphones to online videos illustrating each step in applying the correct amount of pesticides. Designed by R.W. Baldwin, S.K. Hill, Philip Koehler, W. Walker, and J.C. Medley, and published by the UF Department of Entomology and Nematology, August 2012.